2017
DOI: 10.7861/clinmedicine.17-5-412
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a low-fat diet to manage the symptoms of bile acid malabsorption – outcomes in patients previously treated for cancer

Abstract: Dietary fat ingestion triggers bile secretion into the gastrointestinal tract. Bile acid malabsorption affects >1% of the population, causing loose stool and other gastrointestinal symptoms. The diagnosis is frequently missed. Treatments are often considered ineffective. We evaluated low-fat diets for managing gastrointestinal symptoms in these patients. All patients reporting type 6 or 7 stool were offered a selenium-75 homocholic acid taurine (SeHCAT) scan. Prospective data in patients with 7-day scan retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 27 publications
0
41
0
15
Order By: Relevance
“…Symptoms of patients with moderate or severe BAM are stabilised with colesevelam (cholestyramine) first and then the patients are reviewed by the dietitian [ 41 ]. Prospective evaluations of low-fat dietary interventions in managing BAM have demonstrated significant improvements in symptoms, where total fat has been reduced to 20% of daily energy intake [ 42 , 43 ]. Caution is used with patients who have a low body weight or poor oral intake and they are generally commenced on colesevelam in the first instance to optimise their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of patients with moderate or severe BAM are stabilised with colesevelam (cholestyramine) first and then the patients are reviewed by the dietitian [ 41 ]. Prospective evaluations of low-fat dietary interventions in managing BAM have demonstrated significant improvements in symptoms, where total fat has been reduced to 20% of daily energy intake [ 42 , 43 ]. Caution is used with patients who have a low body weight or poor oral intake and they are generally commenced on colesevelam in the first instance to optimise their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A case series with 40 patients has demonstrated that thorough dietary instructions with reduced fat diets have positive impact on these symptoms . A newly published larger study confirm that dietitian instructed low fat diet has an effect of symptoms other than diarrhoea in bile acid diarrhoea …”
Section: Introductionmentioning
confidence: 95%
“…However, no systematic studies of the actual use or effect of bile acid sequestrants in colon cancer survivors have been performed [31]. In addition, no studies have compared the effect of bile acid sequestrants with the effect of a fat-reduced diet [11,32]. Furthermore, one must bear in mind that there are several other gastrointestinal causes of chronic diarrhoea; thus, a systematic clinical evaluation is warranted [8,13].…”
Section: Treatment Effectsmentioning
confidence: 99%